THE ‘SEARCH-FOR METHOD’: EXAMINING INSTANCES OF SUPPORT IN FACEBOOK GROUPS FOR DONOR-CONCEIVED PEOPLE - Newton, Giselle (AoIR Selected Papers of Internet Research, 2020)
Facebook groups represent an important resource for donor-conceived people to access information, seek advice and share their experiences with their peers. Limited research has considered how donor-conceived people create supportive relationships with peers through social media or how this form of social support contributes to donor-conceived people’s health and wellbeing. This work in progress outlines the ‘search-for method’, a practical user-led tool for discussing instances of participation in Facebook groups. The ‘search-for method’ involves inviting participants to search for their name in the search bar of a Facebook group, thereby retrieving data of all instances they have posted in the group. This paper reports on initial findings from applying the ‘search-for method’ to semi-structured interviews with administrators and members (N=30) of Facebook groups for donor-conceived people from across Australia. The ‘search-for method’ enabled the participant and researcher, as co-analysts, to track and examine specific instances of participation and interaction in the group. By scrolling through content on their own device, participants could decide how to frame their stories of support and whether to disclose sensitive information or omit experiences they did not wish to discuss. Broadly, this approach illuminated how individual and collective donor-conceived identities emerged and evolved with and through online group platforms. In doing so, it provided a framework for understanding sociality between donor-conceived peers longitudinally. This paper contributes to understandings of how digital affinities and peer intimacies develop in Facebook groups over time.